Students’ perspectives on quality of engineering education in India (Journal of Applied Learning and Teaching, 2021)
It is widely held that engineering education in India has expanded massively at the cost of quality, quality being perceived in terms of, inter alia, ranking of institutions in the national and global university ranking systems, and employability and attributes of graduates. Evidence on these aspects is based on the perspectives of the policy makers, administrators in higher education and employers in the labour market. Rarely the students’ perspectives on quality of their education are considered in formulating these conclusions. Assuming that students’ perceptions on the quality of education, which may differ from prevailing perceptions of the others, are important and they need to be paid attention to in research and policy making, the attempt in this study is to examine this aspect and fill the gap in research to some extent. Based on a survey of about 7,000 students enrolled in undergraduate engineering studies in 48 public and private institutions in four major states in India, this article presents a contrasting perspective on quality of engineering education in India. The findings are indeed perplexing, as a majority of students are ‘satisfied’ with the quality of education in their institutions, and they are well prepared for the world of work in India or abroad, and/or for further education. These findings will compel the researchers to widen their approach to study quality-related problems of higher education in India, and administrators and policy makers to rethink on their perspectives and associated actions.